Aflibercept in wet age-related macular degeneration: a perspective review - Ohr, Matthew (SAGE Publications, 2012)
In the treatment of neovascular age-related macular degeneration (AMD), vascular endothelial growth factor (VEGF) has emerged as a key target of therapy. Currently, patients with neovascular AMD are treated with monthly intravitreal injections of anti-VEGF medications. Aflibercept is a novel recombinant fusion protein engineered to bind all isoforms of VEGF-A, VEGF-B, and placental growth factor. It is the latest medication to receive US Federal Drug Administration (FDA) approval for the treatment of neovascular AMD. Theoretical models suggest this molecule may have a longer duration of action compared with current treatments. The results of the VEGF Trap-Eye: Investigation of Efficacy and Safety in wet Age-related Macular Degeneration studies (VIEW 1 and VIEW 2) support this by demonstrating that aflibercept, dosed every 2 months after a monthly loading dose for 3 months, was noninferior in the proportion of patients who maintained or improved vision at 52 weeks compared with monthly injections of ranibizumab. These results were maintained over the 2 years of the studies. Aflibercept (Eylea; Regeneron Pharmaceuticals, Inc., Tarrytown, NY, USA and Bayer, Basel, Switzerland) was approved by the FDA for the treatment of neovascular AMD on 18 November 2011.